Entrepreneurship and Human Development: An International Analysis - Camacho Ballesta, José Antonio; Hoz Rosales, Bladimir José de la; Torres, Ignacio Tamayo (Review of Business Management, 2020)
Purpose – This study aims to analyze the impact on human development of rates of innovative entrepreneurship and necessity entrepreneurship. Design/methodology/approach – Our empirical study is based on samples from countries with information about rates of entrepreneurship, human development, and social progress. The data are analyzed by means of pooled least squares and panel data techniques. Findings – Innovative entrepreneurship improves the quality of life in the dimensions measured by the Social Progress Index and Modified Human Development Index. Necessity entrepreneurship does not favor an increase of human development, at least in the dimensions measured by the two indexes, since this is a subsistence entrepreneurship type. Originality/value – This study presents new evidence that contributes to the knowledge on how entrepreneurship improves quality of life.